On the effective evaluation of TCP. - Allman, Mark (Computer communication review.)
Understanding the performance of the Internet's Transmission Control Protocol (TCP) is important because it is the dominant protocol used in the Internet today. Various testing methods exist to evaluate TCP performance, however all have pitfalls that need to be understood prior to obtaining useful results. Simulating TCP is difficult because of the wide range of variables, environments, and implementations available. Testing TCP modifications in the global Internet may not be the answer either: testing new protocols on real networks endangers other people's traffic and, if not done correctly, may also yield inaccurate or misleading results. In order for TCP research to be independently evaluated in the Internet research community there is a set of questions that researchers should try to answer. This paper attempts to list some of those questions and make recommendations as to how TCP testing can be structured to provide useful answers.